BUDAYA MEMBACA SEBAGAI IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI MI MA’ARIF GONDOSULI MUNTILAN - Lailatul Munawwaroh; Samsul Arifin (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
This study aims to describe the implementation of the School Literacy Movement (GLS) at MI Ma'arif Gondosuli Muntilan. This study used a descriptive research design with a qualitative approach. The results showed that there was an implementation of the school literacy movement at MI Ma'arif Gondosuli Muntilan. The implementation includes: (1) adding enrichment books, as for the types of books available from textbooks, references and reading or enrichment books; (2) carrying out the habituation stage of literacy activities, as for activities such as holding reading activities 10-15 minutes before; (3) display of posters, including posters on the environment, traffic safety and invitations to read; (4) reading and writing activities in thematic learning.